Development of local eco-network of Lutsk territorial community: features and problems - Zoia Karpiuk; Vasyl Fesyuk (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2023)
Introduction. Planning of ecological networks at the local level is one of the most difficult stages of geospatial organization of the territory, which requires a detailed and balanced approach, thorough analysis of topographic materials, land management data and the use of geographic information technologies. Local-level eco-networks have a number of features related to the need for a high level of detalization and connectivity of their components. For them, specific model questions are formed about the assignment of certain areas to the structural and functional elements of the ecological network. At the same time, these elements are complementary elements in the structure of ecological networks of regional importance.